Impact of age-related cerebral white matter changes on the transition to disability - the LADIS study: rationale, design and methodology - Pantoni, Leonardo; Basile, Anna Maria; Pracucci, Giovanni; Asplund, Kjell; Bogousslavsky, Julien; Chabriat, Hugues; Erkinjuntti, Timo; Fazekas, Franz; Ferro, José M.; Hennerici, Michael G.; O'brien, John; Scheltens, Philip; et al. (Neuroepidemiology, 2005)
Age-related white matter changes (ARWMC) on brain MRI have been associated with cognitive, motor, mood and urinary disturbances. These factors are known to contribute to disability in elderly people, but the impact of ARWMC and of their progression on the transition to disability is not determined. The LADIS (Leukoaraiosis and Disability in the Elderly) study aims at assessing the role of ARWMC as an independent predictor of the transition to disability in initially nondisabled elderly (65-84 years). Subjects who are not impaired or impaired on only 1 item of the Instrumental Activity of Daily Living (IADL) scale, presenting with different grades of ARWMC severity, were enrolled. Eleven European centers are involved. All the patients were assessed at baseline using an extensive set of clinical and functional tests including global functioning, cognitive, motor, psychiatric and quality of life measures. MRI studies were performed at baseline and will be repeated at the end of the follow-up period to evaluate changes of ARWMC and other lesions. ARWMC were categorized into mild, moderate or severe using the scale of Fazekas et al. For each ARWMC severity class, the primary study outcome is the transition to disability defined as an impairment on 2 or more IADL scale items. Secondary outcomes are the occurrence of dementia, depression, vascular events or death. Six-hundred and thirty-nine subjects (mean age 74.13 +/- 5.0 years, M/F: 288/351) were enrolled in a hospital-based setting and are being followed up for up to 3 years. The large and comprehensive set of measures in LADIS enables a comprehensive description of their functional and clinical features to be examined in relation to different morphological patterns and severity of ARWMC. The longitudinal design will give insight into the possible role of ARWMC and their progression as an independent contributor to disability in the elderly, eventually helping to develop preventive strategies to reduce the burden of disability in late life. The study results may also help to standardize, on an international basis, tools and criteria to identify early stages of disability.